2019
DOI: 10.1111/1750-3841.14932
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Response to Tomato Pomace Powder as an Ingredient in Bread: Impact of Sensory Liking and Benefit Information on Purchase Intent

Abstract: This study evaluated consumer acceptance and purchase intent (PI) for bread formulated with dried tomato pomace powder (DTPP). DTPP was used to substitute 5 or 10% by weight for a 50/50 mix of white and whole-wheat flour used in a control bread. Consumers (n = 231) evaluated sensory attributes and PI on the breads, which were produced and presented as slices from a typical commercial sandwich loaf. Before answering PI questions, panelists were presented with information regarding the DTPP ingredient. Some rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
2
16
2
Order By: Relevance
“…The CIE L*, a*, and b* values were 60.10, 8.27, and 24.67, respectively. Our results were partially agreed with the results of Concha-Meyer et al [48] [4] may be attributed to different colour measurement scales (CIE L* a* b*, and Hunter L a b scales). It can be concluded that the high a* (redness) and b* (yellowness) values of tomato pomaces may be the result of lycopene, β-carotene, lutein, cis-βcarotene, and zeaxanthin as previously identified by Knoblich et al [9].…”
Section: Properties Of Dried Tomato Pomacesupporting
confidence: 92%
See 4 more Smart Citations
“…The CIE L*, a*, and b* values were 60.10, 8.27, and 24.67, respectively. Our results were partially agreed with the results of Concha-Meyer et al [48] [4] may be attributed to different colour measurement scales (CIE L* a* b*, and Hunter L a b scales). It can be concluded that the high a* (redness) and b* (yellowness) values of tomato pomaces may be the result of lycopene, β-carotene, lutein, cis-βcarotene, and zeaxanthin as previously identified by Knoblich et al [9].…”
Section: Properties Of Dried Tomato Pomacesupporting
confidence: 92%
“…An essential indicator of shelf-life stability of any food product, water activity, was found to be 0.356 in dried tomato pomace. Our finding was lower than that of dried tomato pomace powder (0.48) with higher moisture content (5.59%) reported by Concha-Meyer et al [48]. The CIE L*, a*, and b* values were 60.10, 8.27, and 24.67, respectively.…”
Section: Properties Of Dried Tomato Pomacecontrasting
confidence: 79%
See 3 more Smart Citations